Combination of Warm Infusion Fluid and Warm Electric Blanket on the Body Temperature of Patients Post-Sectio Caesarea - Tri Nova Aprianti; Ta'adi Ta'adi; Arwani Arwani; Roro Sri Endang Pujiastuti; Mardiyono Mardiyono (Universitas Muhammadiyah Semarang, 2022)
Sectio Caesarea has various complications during the postoperative period, one of which is a decrease in body temperature, if not handled properly it can cause hypothermia and cause discomfort to the patient. This study aims to determine the effectiveness of the combination of warm infusion fluids and warm electric blankets on the body temperature of post-sectio caesarea patients in the recovery room. This research is a true-experimental study with pretest and post-test with control group design approach. The research sample was divided into 4 groups, each group was given treatment for 60 minutes. The results showed that warm infusion fluids and warm electric blankets were adequate compared to other groups, with p-value = 0.000 (p<0.05). Based on this study, it can be concluded that the combination of warm infusion fluids and warm electric blankets effectively increases the body temperature of post-sectio caesarea patients.